Treadmill training improves lung function and inhibits alveolar cell apoptosis in spinal cord injured rats - Xianbin Wang; Yingxue Fu; Xianglian Yang; Yan Chen; Ni Zeng; Shouxing Hu; Shuai Ouyang; Xiao Pan; Shuang Wu (Scientific Reports)
Abstract Secondary lung injury after SCI is a major cause of patient mortality, with apoptosis playing a key role. This study aimed to explore the impact of treadmill training and miR145-5p on the MAPK/Erk signaling pathway and apoptosis in rats with complete SCI. SD rats were used to establish T10 segmental complete SCI models and underwent treadmill training 3, 7, or 14 days postinjury. Various techniques including arterial blood gas analysis, lung wet/dry weight ratio, HE staining, immunofluorescence staining, immunohistochemical staining, qRT-PCR, and Western blotting were employed to assess alterations in lung function and the expression levels of crucial apoptosis-related factors. In order to elucidate the specific mechanism, the impact of miR145-5p on the MAPK/Erk pathway and its role in apoptosis in lung cells were confirmed through miR145-5p overexpression and knockdown experiments. Following spinal cord injury (SCI), an increase in apoptosis, activation of the MAPK/Erk pathway, and impairment of lung function were observed in SCI rats. Conversely, treadmill training resulted in a reduction in alveolar cell apoptosis, suppression of the MAPK/Erk pathway, and enhancement of lung function. The gene MAP3K3 was identified as a target of miR145-5p. The influence of miR145-5p on the MAPK/Erk pathway and its impact on apoptosis in alveolar cells were confirmed through the manipulation of miR145-5p expression levels. The upregulation of miR145-5p in spinal cord injury (SCI) rats led to a reduction in MAP3K3 protein expression within lung tissues, thereby inhibiting the MAPK/Erk signaling pathway and decreasing apoptosis. Contrarily, rats with miR145-5p knockdown undergoing treadmill training exhibited an increase in miR145-5p expression levels, resulting in the inhibition of MAP3K3 protein expression in lung tissues, suppression of the MAPK/Erk pathway, and mitigation of lung cell apoptosis. Ultimately, the findings suggest that treadmill training may attenuate apoptosis in lung cells post-spinal cord injury by modulating the MAP3K3 protein through miR145-5p to regulate the MAPK/Erk signaling pathway.